Winning independence : the decisive years of the Revolutionary War, 1778-1781 - Ferling, John E. (Bloomsbury Publishing, 2021)
Winning Independence is the dramatic story of how and why Great Britain--so close to regaining several southern colonies and rendering the postwar United States a fatally weak nation--ultimately failed to win the war. The book explores the choices and decisions made by Clinton and Washington, and others, that ultimately led the French and American allies to clinch the pivotal victory at Yorktown that at long last secured American independence.